In Search of the Next Memory Inside the Circuitry from the Oldest to the Emerging Non-Volatile Memories - Gastaldi, Roberto; Campardo, Giovanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides students and practicing chip designers with an easy-to-follow yet thorough, introductory treatment of the most promising emerging memories under development in the industry. Focusing on the chip designer rather than the end user, this book offers expanded, up-to-date coverage of emerging memories circuit design. After an introduction on the old solid-state memories and the fundamental limitations soon to be encountered, the working principle and main technology issues of each of the considered technologies (PCRAM, MRAM, FeRAM, ReRAM) are reviewed and a range of topics related to design is explored: the array organization, sensing and writing circuitry, programming algorithms and error correction techniques are reviewed comparing the approach followed and the constraints for each of the technologies considered. Finally the issue of radiation effects on memory devices has been briefly treated. Additionally someconsiderations are entertained about how emerging memories can find a place in the new memory paradigm required by future electronic systems. This book is an up-to-date and comprehensive introduction for students in courses on memory circuit design or advanced digital courses in VLSI or CMOS circuit design. It also serves as an essential, one-stop resource for academics, researchers and practicing engineers.
Historical overview of solid-state non-volatile memories -- State of art limitations -- New approaches to non-volatile memories -- Core circuitry -- Periphery circuitry -- Functional interfaces -- Error management -- Algorithm to survive -- Final considerations.
Keywords: Electronic circuits; Computer storage devices; Memory management (Computer science).; Semiconductors; Electronics; Electronic Circuits and Systems; Computer Memory Structure; Semiconductors; Electronics and Microelectronics, Instrumentation